LITERATURE REVIEW: OPTIMALISASI SISTEM ABSENSI DIGITAL DALAM MENINGKATKAN PRODUKTIVITAS KERJA (STUDI PADA PT PUPUK KUJANG) - Halimah, Elma; Lumban Batu, Reminta (Jurnal Manajemen dan Bisnis, 2025)
The implementation of digital attendance systems is increasingly common in the industrial sector to improve employee discipline and productivity. PT Pupuk Kujang has adopted this system to optimize attendance tracking and operational efficiency. A literature review of 10 scientific journals shows that digital attendance using biometrics, facial recognition, and geolocation can minimize data manipulation, increase transparency, and simplify attendance reporting. Studies also emphasize that integrating digital attendance with HR systems, offering flexible attendance settings, and providing employee training significantly enhance system effectiveness. However, challenges such as technical issues, user resistance, and infrastructure limitations must be addressed. For PT Pupuk Kujang, optimizing digital attendance can be achieved through cloud-based system development, network infrastructure upgrades, and linking attendance records to incentive policies. By overcoming these challenges, PT Pupuk Kujang can maximize the benefits of its digital attendance system. An effective system not only improves individual accountability but also strengthens overall work productivity and enhances human resource management within the company.